Pathophysiological Role of Hormonal Alterations in Recurrent Urinary Tract Infections among Postmenopausal Women: A Clinical Cross-Sectional Study - Muhammad Asif, Moizza Aziz, Sajida Imran, Rubab Ahmad, Hina Sadaf, FNU Vishal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In postmenopausal women, recurrent urinary tract infections (rUTIs) are common, occurring in most cases due to hormonal changes following the menopause. Urinary microbiota dysbiosis and compromised urothelial integrity have been implicated for estrogen deficiency. Objective: In this study, the role of hormonal alterations, urinary microbiota, and immune markers in predisposing postmenopausal women to rUTI is investigated. Methods: A cross-sectional study was done in n=150 postmenopausal women, n=75 with rUTIs and n=75 controls. ELISA, 16S rRNA sequencing and multiplex immunoassay were used to assess serum hormone levels, urinary microbiota composition and immune biomarkers. T-tests, chi-square tests and logistic regression were used in statistical analysis. Results: Estradiol levels (10.3 ± 3.7 pg/mL vs. 17.6 ± 5.2 pg/mL; p<0.001), Lactobacillus abundance (22.4% vs. 54.1%; p<0.001) were significantly lower in women with rUTIs compared to women without rUTIs. As well, the rUTI group had elevated IL-6 and TNFα levels (p<0.01) and decreased E-cadherin and cathelicidin (p<0.01). Conclusion: rUTIs in postmenopausal women are caused by the combined effect of hormonal alterations, microbiota dysbiosis, and immune dysregulation. These findings underscore the urgent need for personalized therapeutic strategies aimed at these factors. Keywords: Postmenopause, Recurrent urinary tract infections, Hormonal alterations, Estrogen deficiency, Urinary microbiota, Immune biomarkers, Dysbiosis.